Underwater fiber laser removal of synthetically cultured Caulobacter crescentus biofilms on aluminium using response surface methodology - Hawa, Ringkai; Khairul Fikri, Tamrin; Ngui Sing, Ngieng; Abdullah, Yassin; Awang Ahmad Sallehin, Awang Husaini; Jamil, Musel (Springer Nature Limited, 2025)
Biofouling can be considered the accumulation of microorganisms and other organisms on submerged surfaces. It poses operational and economic challenges across marine, industrial, and freshwater systems. Despite its relevance, freshwater biofilm removal remains understudied compared to marine biofouling. This study evaluates the use of fiber laser treatment to remove synthetically cultured Caulobacter crescentus biofilms formed on aluminium substrates submerged in a nutrientrich microbiological growth medium. A response surface methodology was applied to optimize three laser processing parameters: laser power, laser speed, and repetition loops. The aim was to maximize biofilm removal efficiency while minimizing substrate damage. Results revealed that the number of repetition loops was the most significant factor, as multiple repetition loops compensated for energy losses caused by water absorption and the high thermal conductivity of aluminium. While increased laser power enhanced removal, its individual impact was less pronounced, and laser speed had minimal effect due to rapid thermal dissipation and water interference. A distinct white line, visible both macroscopically and microscopically, appeared in some laser-treated areas. Its origin is hypothesized to involve oxidation or material ablation, warranting further analysis. Response surface analysis demonstrated a non-linear relationship between biofilm removal width and both laser power and repetition loops, with peak efficiency observed at intermediate laser power levels. The observed curvature is attributed to the interplay of water turbulence, microbubble formation, and localized heat transfer dynamics. These findings highlight the complex nature of laser–biofilm interactions in submerged environments. This study contributes to the optimization of non-contact laser cleaning techniques for submerged applications and offers practical insights for industries such as water treatment, biomedical device maintenance, and antifouling surface design.